Intranasal interferon as protection against experimental respiratory coronavirus infection in volunteers. - Higgins, P G (1983)
In a double-blind, placebo-controlled study, self-administered intranasal human interferon alpha A produced by recombinant DNA technology was given both before and after virus challenge with a respiratory coronavirus. The incidence of colds, the severity of symptoms and signs, and virus replication were all reduced in subjects receiving interferon as compared with those given placebo.